2023
DOI: 10.3390/v15020511
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus A6 Infection Causes Neurogenic Pathogenesis in a Neonatal Murine Model

Abstract: Coxsackievirus A6 (CVA6), a member of species A enterovirus, is associated with outbreaks of hand-foot-and-mouth disease and causes a large nationwide burden of disease. However, the molecular pathogenesis of CVA6 remains unclear. In the present study, we established a suckling Institute of Cancer Research (ICR) mouse infection model to explore the neural pathogenicity of CVA6. Five-day-old mice infected with CVA6 strain F219 showed lethargy and paralysis, and died 5 or 6 days after infection via IM injection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The role of USP18 in viral infectious diseases, particularly those related to the central nervous system (CNS), has been the focus of previous research ( 33 , 34 ). The role of USP18 in the IFN pathway has therefore encouraged research in the field of malignant tumors ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of USP18 in viral infectious diseases, particularly those related to the central nervous system (CNS), has been the focus of previous research ( 33 , 34 ). The role of USP18 in the IFN pathway has therefore encouraged research in the field of malignant tumors ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a nucleic acid sensor, the Zα domain of ZBP1 triggers inflammatory response by binding to Z-conformational nucleic acids (Z-DNA/ Z-RNA) [29], however, whether SVA can form Z-RNA during replication needs to be further tested. In addition, the expression of ZBP1 is upregulated in the infection of a variety of viruses, such as influenza virus [30], coxsackievirus A6 [31], and HSV-1 [17]. ZBP1 is also considered to be a limiting factor of HSV-1, indicating that ZBP1 is an important antiviral molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, the majority of EV71-associated HFMD outbreaks occurred in China among the Asia–Pacific countries [ 10 ]. Recent epidemic analysis has shown that CV-A6 has replaced CV-A16 and EV-A71 as the leading epidemic serotypes in many provinces of China [ 11 ]. This demonstrates that CV-A6 is a major cause of HFMD in patients after the launch of EV-A71 vaccination in Chengdu [ 12 ].…”
Section: Introductionmentioning
confidence: 99%